Effects of electrical conductivity of irrigation water on the growth and production of Solanum lycopersicum L. var. cerasiforme grown in greenhouse - Marchese M.; Tuttobene R.; Restuccia A.; Longo A.M.G.; Mauromicale G.; Restuccia G. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
It was found that the negative effects of salinity on tomato become apparent with electrical conductivity values of the circulating solution starting from 2.5 - 3.0 dS m-1 for the fruits, from 4.5 - 5.0 dS m-1 for the stems and leaves and from 6.0 dS m-1 for the roots. The aim of the research was to study in tomato var. cerasiforme Naomi cultivated in greenhouse, the residual effects of irrigation carried out for 10 consecutive years with saline water. At 75 - 90 and 105 days after transplantation, five plants and corresponding soil samples from 0 to -40 cm, were collected from each plot. On each plant, the number and the weight of marketable fruits per cluster and the epigeal biomass dry weight were recorded. On each soil sample the electrical conductivity of extract saturated (ECe) was determined. The use of irrigation water with ECw fluctuating around 2.0 dS m-1 over a decade, determined values of ECe in the soil above the tolerance limit only for the fruit production (3.8 compared to 2.5 - 3.0 dS m-1). With ECw equal to 6.0 + 10.0 dS m-1, levels of ECe exceeded those considered detrimental to the production of dry epigeal biomass. The effects of increasing ECe on the fruit production were constantly determined through the reduction of fruit dry unit weight.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)